Easy and New Chemical Synthesis of Stable Nano Sliver using Propylene Glycol and Glycerin as Reducing Agents - Abdulah Mohammed; Sarab Mahmood (Engineering and Technology Journal, 2018)
In this present work we have synthesized stable silvernanoparticles (Ag-NPs) by chemical reduction with aqueous solutions ofsilver nitrate (i) propylene glycol (ii) glycerin as reducing agents and guargum as a stabilizer. The reaction were done at room temperature and atpH=8. Systematic characterizations of the Ag-NPs were done using UV-Vis,zeta potential analysis, X-Ray diffraction (XRD), AFM and SEM whichreveal stable Ag-NPs. These measurements indicate that the particles aremostly spherical in shape. The UV-Vis spectra of the result solution of Ag-NPs show an absorption peak at 412 nm and 424 nm for using propyleneglycol and for using glycerin respectively. These color occurring due toSurface Plasmon Resonance (SPR). The SEM measurements gave a particlesize of 40 -70 nm. Nano silver showed stability for long periods of time tomore than nine months, and this can be an economical and effective way forwide scale synthesis of Ag-NPs which applicable for various medicaltherapies.